Funkcje gospodarcze samorządu terytorialnego - Patrzałek, Leszek (Wydział Prawa i Administracji UAM, 1991)
In the light of the provisions of the Act on Territorial Self-Government communal organs should change their role of passive executors of central government policies into the role of active and independent decision-makers and organizers who determine and implement local developmental policies. However, recent research into the present state of functioning of local organs shows that they meet considerable obstacles in carrying out their economic functions. The research has been carried out by means of inquiries conducted with communal officers of selected territorial units in Lower Silesia. Besides, factor analysis combined with the elements describing causal relations has also been used. The latter method was applied to the interpretation of legal acts and statistical materials. The research shows that to the basic impediments in carrying out economic functions belong: 1) inefficiency of a decision-making system in the sphere of local zoning policy; 2) the shortage of financial resources in local budgets; 3) gaps and the lack of coherence in the system of economic instruments used by local authorities. The above problems and general conclusions resulting from the analysis are the subject-matter of the present article.
Economic functions of territorial self-government